The Basis for the Effective Strategy for Development of Local Labour Market - Ziomek , Agnieszka (Studia Oeconomica Posnaniensia, 2016)
In this paper, an attempt at verification of possibility of foresight implementation was undertaken. Implementation focuses on a long-term strategic planning methodology for the local labour market. The author accepts that the foresight approach and strategic planning for the local labour market covers such coherent areas as: multilayer field of analysis, necessity of holistic and systemic approach, and the rule of long term vision analysis. On this basis, it is possible to implement planning work with advanced prediction tools. Foresight was developed for large companies in the 1950s, and now is at the level of economic policy and self-government planning. The accuracy of forecasts and speeding up the development by eliminating erroneous paths brings the desired effects of local government policies to the local labour market. The study provides an example of an extracted four scenarios for the labour market in gminas, rich in brown coal in Wielkopolska, to show how to make a decision about the right shape of a development strategy in those communities, supported by the modelling plans, and based on the diagnosis of trends and changes in the future.